The Using of Mungbean Sprouts Extract as Nitrogen Sources in the Making of Nata De Pina from Pineapple Peel - Prawira, Hardy; Pato, Usman; Ayu, Dewi Fortuna (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2022)
Nata is a fermentation product of Acetobacter Xylinum bacteria. The addition of mung bean sprout extracts had a role in the nitrogen needs into nata de pina's medium as the growth of A. xylinum. This research aimed to study the use of mung bean sprouts extract optimally on the characteristics of nata de pina from the pineapple peel. The study used a completed randomized design (CRD) that consisted of 4 treatments and 4 replications. The data obtained were statistically analyzed by using analysis of variance (ANOVA) and continued with Duncan's New Multiple Range test (DNMRT) at α 5% of significant probability. The treatment in this research was the concentration of mung bean sprouts extract on the volume of pineapple peel extract, namely TN1 (8%), TN2 (10%), TN3 (12%), and TN4 (14%). As a result, the difference in concentration of mung bean sprout extract gave a significantly different effect on thickness, yield, water content, the descriptive and hedonic test of color, also the hedonic test on taste and overall assessment of the nata. However, the addition of mung bean sprouts extract into nata de pina's medium has not a significant effect on the descriptive and hedonic test of flavor, texture, and the descriptive test on the taste of the nata. The best nata de pina's formula was TN4 with a thickness of 4.42 mm, a yield of 16.96%, the water content of 84.56%, a dry weight of 59.21%, a rather white color, somewhat acidic flavor, chewy texture, and plain taste.